Perencanaan Pembelajaran Berdiferensiasi untuk Mengakomodasi Keberagaman Peserta Didik di Sekolah Dasar - Dwi Anggina Pasha; Alisah Amanda; Anggina Hasanah Putri; Dina Aulia; Selsy Abrilya; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
The diversity of learning styles among elementary school students is a reality that cannot be ignored in educational practice. A homogeneous teaching approach fails to accommodate individual differences, resulting in marginalization of learners, demotivation, and widening achievement gaps. This article discusses the implementation of differentiated curriculum as a strategic approach in lesson planning using a literature review method. Through a systematic review of relevant literature, three main dimensions of differentiation are identified: content, process, and product differentiation. The analysis reveals that teachers applying differentiated instruction significantly improve student engagement and learning outcomes. Key challenges include limited planning time, administrative burdens, and insufficient professional training. This article recommends teacher competency development, strong institutional support, and stakeholder collaboration as keys to successful implementation